Integrasi Nilai Akhlak Mulia dalam Budaya Minangkabau Pada Mata Pelajaran PAI BP - Ermiyanto; Fadriati (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2023)
Character education in educational institutions is the foundation in moral development. Islamic Religious Education Materials (PAI) and Budi Pekerti (BP) are learning materials that are very relevant to moral development in schools. Moral learning cannot be separated from the culture of the school environment. Minangkabau culture that developed through Islamic culture has moral values ​​as evidenced by several moral terms that are relevant to Minangkabau expressions. The integration of PAI BP learning with Minangkabau culture needs to be done in the context of developing and strengthening the morals of students. The method used in this study is a literature review sourced from 15 national journals and 3 international journals published between 2018 and 2022. The journals were selected from Google Schoolar with the keywords "moral integration in learning", "Minangkabau culture in moral learning", and "humanistic theory in moral learning". The results of the study show that the integration of PAI BP learning with moral values ​​in Minangkabau culture can be done by preparing lesson plans using a humanistic theory approach. The planning stage of learning both preparation, implementation and evaluation must contain elements of morals.